Ornithological Survey and Habitat Quality Study in Rara Lake, Nepal - Shrestha, Mohan Bikram; Nepal, Kriti; Magar, Tek Bahadur Gharti; Rijal, Deepak (Journal of Environment Sciences, 2022)
Rara Lake is situated in mountain ecoregion serves as staging post for the long range migratory wetland birds. The lake ambient forest bears the restricted range and globally threatened species. Bird species in the park is reported as unrecorded while habitat quality of the Rara lake providing the refuge to migratory and native bird species is degrading. Adherence to the statement, study was carried to gather the descriptive and evidence- based information on bird species and habitat quality was carried to understand bird status, its activities and habitat quality. Bird count was carried through line transect. Bird behavior, activities, stay-length and lake riparian habitat was noted through direct sighting. Water quality was assessed following American Public Health Association water quality test guideline. The study counted a total of 2415 bird individuals from listed 104 species including 16 migratory Waterfowls, 13 wetland dependent birds and 75 forest birds. The observed bird species ranged from frequent to very uncommon winter visitor stop in Rara lake primarily for fueling during migration. Observed that most of time birds were foraging at shallow water but merely outside lakes. Discarded trashes in the roosting and foraging site and around the lake circuit trail triggering threats to waterfowls and aquatic biodiversity while higher human movement through the trail causing disturbance to waterfowl. Water quality assessment revealed that Phosphorous and ammonia concentration in Rara lake were higher than the recommended level for freshwater/aquatic ecosystem connoting lake in the process of eutrophication and acute ammonia toxicity affecting aquatic life. Regular assessment of water quality is required preventing aquatic life from detrimental effects. Continuous monitoring to study their migratory behavior and habitat qualities would be essential to inform conservation policies also linking with eco-tourism activities.